Educational justice : challenges for ideas, institutions, and practices in Chilean education - Moyano Dávila, Camila (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"This book presents a novel perspective on education as a social right. Literature on this topic has focused on inclusion as the universal concept whereby access to education is examined. As a moral principle, this concept opens new challenges in different ways if we take a deeper view into diverse contexts. What education? For what? For whom? Are we thinking about education because it will bring social justice in the future, or are we thinking of education as a just practice in the present? This book brings fresh theoretical and empirical perspectives on those questions, moving beyond a pure inclusion paradigm to a broader and context-oriented notion of educational justice. The chapters engage with theories of educational justice to present these challenges at the institutional level of educational policy, at the practical level of schooling practices, and in the production of ideas around childhood and education, for instance, notions of normalcy at schools. Although the featured works are related to the Chilean educational system, they opens questions about education in general. They embrace rural and urban contexts, different educational levels (from preschool to university), and university and vocational education. This book will be rewarding reading for educational scholars, those interested in theories of social and educational justice, and anyone interested in contemporary perspectives on education, childhood and youth, inclusion, and justice"-- Provided by publisher.
Keywords: Social justice and education -- Chile.; Education -- Social aspects -- Chile.; Education -- Philosophy, Theory & Social Aspects.; Human rights, civil rights.; Philosophy and theory of education.; elektronické knihy; electronic books